Tetraploids, triploids and 2n pollen from diploid interspecific crosses with cassava - Hahn, S.K.; Bai, K.V.; Asiedu, Robert (Springer, 1990)
Interspecific crosses of five cultivated cassava varieties (2n=36) were made with two related Manihot species, M. epruinosa (2n=36) and M. glaziovii (2n=36). From these diploid interspecific crosses, four spontaneous tetraploids (2n=4x=72) and two triploids (2n=3x=54) were isolated for the first time in cassava. Occurrence of relatively high frequencies (0.1%–35.6%) of 2n pollen and of apomixis seems to be associated with sexual polyploidization. The tetraploids and triploids were very vigorous and one of the tetraploids performed as well as the best variety in uniform yield trials conducted in Nigeria. These spontaneous polypoloids provide greater genetic variation and offer an opportunity to breed radically new cassava varieties. Approaches for isolating and utilizing the polyploid cassava clones for varietal and population improvement are discussed.